From time to space: the impact of aspectual categories on the construal of motion events : the case of Tunisian Arabic and modern standard Arabic - Stutterheim, Christiane von; Bouhaous, Abbassia; Carroll, Mary (De Gruyter, 2018)
Motion events and their linguistic form have been studied extensively over the past decades from a typological as well as a psycholinguistic point of view. While many studies take Talmy’s (1985. Lexicalization patterns: Semantic structure in lexical forms. In Timothy Shopen (ed.), Language typology and syntactic description: Grammatical categories and the lexicon, vol. 3, 57-149. Cambridge: Cambridge University Press, 2000. Toward a cognitive semantics. Cambridge: MIT Press) distinction as the starting point of their theoretical considerations, this twofold, lexicon-based typology has since been extended to capture the range of variation which languages display. Although the specifics of motion event conceptualization entail other factors in addition to space and lexical form, there are few studies on the implications of temporal categories. The aim of the present study is to document the role of aspectual categories in the construal of motion events, as observed in Tunisian Arabic (TA) and Modern Standard Arabic (MSA), two closely-related varieties with relevant contrasts in the types of verbal aspectual categories they encode. The analysis is based on descriptions of different types of motion events elicited on the basis of video clips. The findings reveal basic differences in the spatial and temporal categories selected for encoding-differences which are rooted in the respective linguistic systems: while TA, in contrast to MSA, has fewer forms to express directed motion via spatial concepts (path verbs, prepositions), its aspectual system is richer. The comparison indicates how the expression of directed motion in spatial terms in MSA is conveyed via temporal aspect (progression) in TA. In conclusion, the study outlines the case for the inclusion of temporal categories, in particular grammaticalized aspect, in approaches to the typology of motion events.
Aus: Linguistics, 55 (7 January 2017), Nr. 1. pp. 207-249. ISSN 0024-3949